Circulating Microrna-22 As a Biomarker Related to Oxidative Stress in Hyperthyroid Women Patient - Ali Abd, Zahraa; Jabbar, Nawal (Journal of Biomedicine and Biochemistry, 2023)
Background Recent studies have connected microribonucleic acid (miRNA) to several illnesses as a stimulant or inhibitor. Oxidative stress and thyroid diseases are connected to miRNA-22. The underlying pro- cesses remain unknown. In this study, hyperthyroid women’s miRNA-22 expression is linked to oxidative stress.Materials and Methods 40 women suffering from hyperthyroidism and 40 in this study, healthy volunteers who served as controls were in- cluded. The levels of serum thyroid-stimulating hormone (TSH) were mea- sured by sandwich assay, While the competitive binding immunoenzymatic assay was used to determine the levels of free triiodothyronine (FT3) and thyroxine (T4). To assess lipid profiles, an automated analyzer was em- ployed. By enzyme-linked immunosorbent assay (ELISA), Interleukin 6 (IL-6) levels were measured. Activity of superoxide dismutase (SOD), catalase activity (CAT), (MDA) malondialdehyde, and levels of advanced oxidation protein products (AOPPs) assessed using a colorimetric tech- nique. The quantitative polymerase chain reaction was used to evaluate the expression of serum miRNA-22.Results  Non-significantly increase SOD and significantly increase CAT activity were identified in patient groups than in the control group (P